Green to blue-green-emitting cationic iridium complexes with a CF3-substituted phenyl-triazole type cyclometalating ligand: synthesis, characterization and their use for efficient light-emitting electrochemical cells. Issue 23 (21st May 2021) - Yu, Renyou; Song, Yongjun; Chen, Mengzhen; He, Lei
Abstract : Highly efficient green to blue-green-emitting cationic iridium complexes were developed with 4-diphenyl-5-(trifluoromethyl)-4 H -1, 2, 4-triazole as the cyclometalating ligand. Abstract : Green to blue-green-emitting cationic iridium complexes free of sp 2 C–F bonds, namely [Ir(CF3 -dPhTAZ)2 (bpy)]PF6 (1 ), [Ir(CF3 -dPhTAZ)2 (dmebpy)]PF6 (2 ) and [Ir(CF3 -dPhTAZ)2 (phpyim)]PF6 (3 ), have been designed and synthesized with 3, 4-diphenyl-5-(trifluoromethyl)-4 H -1, 2, 4-triazole (CF3 -dPhTAZ) as the cyclometalating ligand (C^N) and 2, 2′-bipyridine (bpy), 4, 4′-dimethyl-2, 2′-bipyridine (dmebpy) or 2-(1-phenyl-1 H -imidazol-2-yl)pyridine (phpyim) as the ancillary ligand (N^N). In CH3 CN solution, complexes 1–3 afford green to blue-green emission centered at 521, 508 and 498 nm, respectively. The electron-withdrawing CF3 group attached at the triazole ring in CF3 -dPhTAZ largely blue-shifts (by over 20 nm) the emission of the complex through stabilizing the highest occupied molecular orbital. In doped films, the complexes afford sky-blue emission with near-unity phosphorescent efficiencies. In neat films, the complexes show largely suppressed phosphorescence concentration-quenching, with phosphorescent efficiencies of up to 0.66. Theoretical calculations reveal that the emission of the complexes can arise from either charge-transfer (Ir → C^N/C^N → N^N) or C^N/N^N-centered 3 π–π* states, depending on the local environment of the complexes. Solid-state light-emitting electrochemical cells (LECs) based on the complexes afford green to blue-green electroluminescence centered at 525, 517 and 509 nm, respectively, with high current efficiencies of up to 35.1 cd A −1 . The work reveals that CF3 -dPhTAZ is a promising C^N ligand free of sp 2 C–F bonds for constructing efficient cationic iridium complexes with blue-shifted emission.